Media Sosial Baru dan Munculnya Revolusi Proses Komunikasi - NURUDIN NURUDIN (Universitas Muhammadiyah Yogyakarta, 2013)
The study entitled “New Social Media and The Emergence of Revolution in Communication Process” has a background as follows; (1) the people around the world are infatuated with social media, (2) social media has changed the process of message delivery in the world. The social media has even changed the political map, world power, world intercommunication because of the acceleration of communication, and (3) the circulation of information which spreads by social media is much more complicated, more complex, and it has real consequences in internet age today. Based on this study, it could be concluded as follows; (1) the changes in message delivery process from one direction (one-step flow) to the many direction (multistep flow), (2) the amount of message circulation which spreads in the world as a result of social media is greatly increasing beyond space and time, (3) our society is experiencing spillover of communication (overwhelming information) that causes cultural shock in our society. Keywords: Social Media, Revolution, Communication Process